The nationalization of the scientific and technological sphere of the Russian Federation: problems and consequences - Kurakova, N. G. (Economics of Science, 2018)
It is noted that the interim results of the achieved structural changes and the level of technological renewal of the Russian economy make it relevant to reassess the effectiveness of innovative practices and models used in the Russian Federation. The basic provisions of modern science and technology policy are analyzed. The absence of a direct dependence of the level of scientific and technological development of the country on the level of development of the national research and development sector is substantiated. It was recommended to develop a set of measures of modern science and technology policy aimed at reducing the nationalization of the scientific and technological sphere and targeting large and medium-sized companies in the real sector of the economy as the main subjects of the «technological breakthrough».